A review of steganographic methods and techniques - Beroual, Abdessalam; Alshaikhli, Imad Fakhri Taha (Kulliyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
The frequent and intensive transmission of information on the internet requires protection techniques to secure sensitive information. Steganography is one of many security techniques that consist of concealing information inside an appropriate multimedia (e.g. image, video, audio…etc.) with the objective to hide the embedded information. Many challenges confront steganography systems like capacity (size of data embedded) and imperceptibility (level of undetectability). These two aspects are inversely proportional to each other which produces a data hiding dilemma. This paper presents a review of the steganography methods used in recent years and a critical analysis based mainly on capacity measurement and, secondly, on imperceptibility measurement and steganography domain.